Prolonged QTc: "Mind the Gap" (Bangladesh Critical Care Journal, 2014)
We report a case of drug induced torsades de pointes, following acquired long QT syndrome. The patient got admitted for shock with acute abdomen. The initial prolonged QT-interval was missed, and a torsadogenic drug was introduced post-operatively. Patient developed torsades de pointes followed by cardiac arrest. She was managed well and discharged without complications. The clinical manifestations of long QT syndromes, syncope or cardiac arrest, result from torsades de pointes. As syncope or cardiac arrest have more common differential diagnoses, even the symptomatic long QT syndrome are commonly missed or misdiagnosed. In acquired long QT syndrome with no prior suggestive feature, it is not impossible to miss the prolonged QT-interval on the ECG tracing. We share our experience so that the clinicians, especially the junior doctors, will be more alert on checking the QT-interval even in asymptomatic patients. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19970 Bangladesh Crit Care J March 2014; 2 (1): 44-45